Why the Rankings are Wrong: Lessons from Data Underlying U.K. University League Tables - Grayson, J. Paul; Grayson, Kyle (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2026)
This article uses high-quality data from the United Kingdom to critically examine the assumptions underpinning university league tables in Canada and elsewhere. Particular attention is given to research quality and value added in learning (VA). Unlike many global ranking systems, U.K. rankings incorporate measures that allow for robust assessment. Based on these data, we show that league table positions in the United Kingdom are weakly associated with research quality and largely unrelated to VA. Furthermore, research funding bears little consistent relationship to research quality. At both institutional and departmental levels, notably in Politics and International Studies, highly ranked universities do not necessarily deliver superior learning outcomes or research quality. These findings challenge the validity of using inputs such as research grants or student awards as proxies for institutional quality. Although U.K. data cannot be generalized automatically, they provide a valuable reference point for other countries. As a result of these findings, we argue that Canadian rankings, and others like them, must be treated with considerable skepticism.